An effective feature extraction method for fingerprint image - AbdelQader, Hasan; Babiker, Elsadig; Ramli, Abdul Rahman; Al-haddad, Syed (2005)
Biometrics is a technology, which identifies a person based on his physiology or behavioral characteristics. Fingerprint recognition is one of the biometrics methods available that has been widely used in many applications. This paper introduce an efficient method for the recognition of fingerprint images based on features extraction (Minutiae such as ridge bifurcation and ridge ending) from the Zernike Moments, the minutiae are extracted directly from binary image, after the image has been processed, it would then be fed into the back propagation neural network as input in order to train the network, after training, the neural network is ready to perform the recognition operation for minutiae features.